INTERNAL AUDIT FUNCTION AND PUBLIC SERVICE QUALITY : EVIDENCE FROM INDONESIAN LOCAL GOVERNMENTS - Sutaryo, Sutaryo; Salawati, Sahari; Shaharudin, Jakpar; Sophee Sulong, Balia (National Research University High School of Economics (NRU HSE), 2022)
. Th is study investigates the role of local government internal audit function maturity and expertise in supervising local government public service quality. We use secondary data from all local governments in Indonesia for the 2016–2019 fi scal year that generates panel data with 1934 observations, analyzed with panel data regression. Local governments in Indonesia have a good average quality of public services. In most tests, we evidence the positive eff ect of local government internal audit function maturity and expertise on public service quality. Internal audit function maturity is the strongest contributor, while expertise supports the audit process to achieve higher public service quality. Our study provides implications for local government supervision that should be maximized through internal audit function to achieve good quality public services, by developing proper internal auditor programs of the Financial and Development Supervisory Agency (BPKP). Th e local government should also have a proper budget allocation for public service. Th e adoption of information technology should also be optimized in public service implementation and supervision. Finally, our study brings signifi cant novelty to public service and internal audit literature in Indonesia by providing one of the fi rst comprehensive studies covering all Indonesian local governments.